Rising above the torrents - Begum, Khadija; Ilyas, Nouman; Hussain, Kashif; Jamal, Amjad (International Water Management Institute, 2024)
The gender dynamics, community strategies, and vulnerabilities in South Punjab’s hill torrent floods.